One-stage revision is as effective as two-stage revision for chronic culture-negative periprosthetic joint infection after total hip and knee arthroplasty: a retrospective cohort study. (2nd March 2020) - van den Kieboom, Janna; Tirumala, Venkatsaiakhil; Box, Hayden; Oganesyan, Ruben; Klemt, Christian; Kwon, Young-Min
Abstract : Aims: Removal of infected components and culture-directed antibiotics are important for the successful treatment of chronic periprosthetic joint infection (PJI). However, as many as 27% of chronic PJI patients yield negative culture results. Although culture negativity has been thought of as a contraindication to one-stage revision, data supporting this assertion are limited. The aim of our study was to report on the clinical outcomes for one-stage and two-stage exchange arthroplasty performed in patients with chronic culture-negative PJI. Methods: A total of 105 consecutive patients who underwent revision arthroplasty for chronic culture-negative PJI were retrospectively evaluated. One-stage revision arthroplasty was performed in 30 patients, while 75 patients underwent two-stage exchange, with a minimum of one year's follow-up. Reinfection, re-revision for septic and aseptic reasons, amputation, readmission, mortality, and length of stay were compared between the two treatment strategies. Results: The patient demographic characteristics did not differ significantly between the groups. At a mean follow-up of 4.2 years, the treatment failure for reinfection for one-stage and two-stage revision was five (16.7%) and 15 patients (20.0%) (p = 0.691), and for septic re-revision was four (13.3%) and 11 patients (14.7%) (p = 0.863), respectively. No significant differences were observed between one-stage and two-stage revision for 30- 60- and 90-day readmissions (10.0% vs 8.0%; p = 0.714; 16.7% vs 9.3%; p = 0.325; and 26.7% vs 10.7%; p = 0.074), one-year mortality (3.3% vs 4.0%; p > 0.999), and amputation (3.3% vs 1.3%; p = 0.496). Conclusion: In this non-randomized study, one-stage revision arthroplasty demonstrated similar outcomes including reinfection, re-revision, and readmission rates for the treatment of chronic culture-negative PJI after TKA and THA compared to two-stage revision. This suggests culture negativity may not be a contraindication to one-stage revision arthroplasty for chronic culture-negative PJI in selected patients.